2016
DOI: 10.1016/j.cub.2015.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Re-calibration of Perceived Size in Fovea and Periphery through Predictable Size Changes

Abstract: The same object produces quite distinct images in the cortical representation, depending on whether it is looked at foveally or with the periphery, yet some form of size constancy prevents us from experiencing objects inflating or deflating as we move our eyes. According to the prominent sensorimotor account of vision by O'Regan and Noë [1], we constantly learn to discount the predictable sensory effects of motor actions, such as the projection of a stimulus on a larger cortical area as it gets foveated. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
103
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(121 citation statements)
references
References 32 publications
15
103
3
Order By: Relevance
“…Adaptation also took place, even though much less, when the association between fovea and periphery was established through visual motion, without making eye movements. There was no reverse recalibration when changing the size of the stimulus that was in the fovea initially (Valsecchi & Gegenfurtner, 2016). These results show the importance of basic prediction mechanisms for visual perception.…”
Section: Size Perception and Recalibrationmentioning
confidence: 62%
See 3 more Smart Citations
“…Adaptation also took place, even though much less, when the association between fovea and periphery was established through visual motion, without making eye movements. There was no reverse recalibration when changing the size of the stimulus that was in the fovea initially (Valsecchi & Gegenfurtner, 2016). These results show the importance of basic prediction mechanisms for visual perception.…”
Section: Size Perception and Recalibrationmentioning
confidence: 62%
“…It was clearly below the threshold for detecting such changes, as determined by separate measurements. Figure 6 shows that our manipulation did have an effect on the relative perceived size of the peripheral stimulus, before making the saccade (Valsecchi & Gegenfurtner, 2016). After 500 trials, the relative size of the peripheral discs changed by about 5% on average or half of the 10% physical size change.…”
Section: Size Perception and Recalibrationmentioning
confidence: 93%
See 2 more Smart Citations
“…One source of visual stability may be the integration of pre- and post-saccadic visual information (Helmholtz, 1867; Melcher, 2011; Wurtz, 2008). Recent gaze-contingent experimental designs have revealed that orientation (Ganmor et al, 2015; Wolf and Schütz, 2015; Zimmermann et al, 2017), object size (Valsecchi and Gegenfurtner, 2016), visual motion (Fabius et al, 2016), and whole-object information (Castelhano and Pereira, 2017; Schut et al, 2016) are integrated across saccades in a statistically optimal fashion taking into account the relative reliability of pre-saccadic and post-saccadic input (Ganmor et al, 2015; Herwig, 2015; Wolf and Schütz, 2015). Nonetheless, the time-course of trans-saccadic perception and, in particular, the content of perception immediately after fixation-onset remain controversial (for review, Melcher and Morrone, 2015)…”
Section: Introductionmentioning
confidence: 99%